High-density and low-density lipoproteins and prevalence of vascular disease in diabetes mellitus. Issue 6117 (8th April 1978) - Reckless, J P; Betteridge, D J; Wu, P; Payne, B; Galton, D J
Abstract : The prevalence of vascular disease among 154 diabetic patients was analysed in relation to the serum concentrations of individual lipoproteins. Overal the presence of vascular disease (59 cases) was positively associated with serum cholesterol and low-density-lipoprotein cholesterol but negatively associated with high-density-lipoprotein (HDL) cholesterol. The negative relation between HDL and vascular disease was not observed in all subgroups of diabetics. We conclude that there may be no overriding association between HDL and vascular disease in diabetics as proposed for some non-diabetic populations.